1995
DOI: 10.4039/ent127145-2
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Female Southern Pine Beetle Size and Lipid Content in Relation to Fungal Associates

Abstract: Female southern pine beetles, Dendroctonus frontalis Zimmermann, may propagate two species of symbiotic fungi in a prothoracic mycangium. Females can carry either Ceratocystiopsis ranaculosus Bridges and Perry or an unnamed basidiomycete or both; some carry no fungi. Thus, females can be categorized into one of four groups based on mycangial content. We examined size and lipid content of emerging brood adult females based on these mycangial fungal classes. Female beetles carrying the basidiomycete, either alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…The relative prevalence of each of these fungi has a substantial impact on host population dynamics. Individuals that develop with Entomocorticium are larger and have higher lipid contents than those that develop with C. ranaculosus (Coppedge et al 1995), and beetle populations with a higher prevalence of Entomocorticium exhibit more rapid population growth (Bridges 1983;Goldhammer et al 1990;Coppedge et al 1995). In contrast, as the prevalence of the antagonist, O. minus, increases, beetle populations decrease.…”
Section: Forest/savanna Insect-microbe Mutualisms Affected By Anthropmentioning
confidence: 99%
“…The relative prevalence of each of these fungi has a substantial impact on host population dynamics. Individuals that develop with Entomocorticium are larger and have higher lipid contents than those that develop with C. ranaculosus (Coppedge et al 1995), and beetle populations with a higher prevalence of Entomocorticium exhibit more rapid population growth (Bridges 1983;Goldhammer et al 1990;Coppedge et al 1995). In contrast, as the prevalence of the antagonist, O. minus, increases, beetle populations decrease.…”
Section: Forest/savanna Insect-microbe Mutualisms Affected By Anthropmentioning
confidence: 99%
“…This idea is developed in subsequent sections. In contrast, a number appear to be obligate mutualisms in which the bark beetles rely on nutritional supplementation from fungi (5,11,15,23,93). At least some mutualistic partners exhibit parallel cladogenesis with their hosts, indicating long coevolutionary histories (87,93).…”
Section: Bark Beetle-fungus Symbiosesmentioning
confidence: 99%
“…At least some mutualistic partners exhibit parallel cladogenesis with their hosts, indicating long coevolutionary histories (87,93). In these associations, larvae that feed on phloem colonized by mutualistic fungi are larger, more likely to complete development, have higher fecundity, and develop more rapidly than bark beetles that do not (5,11,23,93). For at least one bark beetle species, feeding on fungal spores by new adults appears to be required for reproduction (93).…”
Section: Bark Beetle-fungus Symbiosesmentioning
confidence: 99%
“…A produces lignocellulose-degrading enzymes including cellulase and polyphenol oxidase. Previous studies have indicated that SPB larvae feed on fungal hyphae and spores, although none have been able to explicitly demonstrate this (Coppedge et al, 1995;Klepzig and Wilkens, 1997;among others). Guts of SPB appear to contain little in the way of either undigested cellulose or cellulolytic bacteria (Delalibera et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…After the eggs hatch the early instar larvae feed, constructing, sinuous galleries which terminate in obovate "feeding chambers" (Payne et al, 1983). Within these chambers can be found growth of SPB associated, nutritionally mutualistic fungi (Coppedge et al, 1995). Although many fungi have been associated with galleries of SPB in pine phloem, three have been the focus of most SPB-fungal research, and appear to have the most * The author to whom correspondence should be sent.…”
Section: Introductionmentioning
confidence: 99%